HUBUNGAN MINAT DAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR EKONOMI DI SMA NEGERI KABUPATEN KONAWE SELATAN - Selfi Melianti Alfi (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
This study aims to analyze and explain whether there is a relationship between: (1)learning interest with student economic learning outcomes, (2) learning discipline withstudent economic learning outcomes, and (3) student learning interest and learningdiscipline together- the same as student economic learning outcomes. Survey method withthe correlational approach as a method. The population was 413 students and the samplewas 81. Data collection used instruments. This study found that: (1) there was a positiveand significant relationship between learning interest with students' economic learningoutcomes which were shown correlation coefficient (ry1) 0.675 and deteminationcoefficient 0.4556; (2) there is a positive and significant relationship between learningdiscipline with students' economic learning outcomes shown by the correlation coefficient(ry2) 0.576 and the coefficient of detemination 0.3318; and (3) there is a positive andsignificant relationship between student learning interest and student learning disciplinetogether with student economic learning outcomes shown by the multiple correlationcoefficient (Ry12) 0.720 and the coefficient of detemination 0.5184. That means that thebetter the interest in learning and the discipline of learning, the better the results of studentlearning.Keywords: Learning Interest, Learning Discipline, and Economic Learning Outcomes